The Effect of Noseband Tightening on Horses’ Behavior, Eye Temperature, and Cardiac Responses - Fenner, Kate; Yoon, Samuel; White, Peter; Starling, Melissa; McGreevy, Paul (PLOS ONE, 2016)
Restrictive nosebands are common in equestrian sport. This is concerning, as recent evidence suggests that very tight nosebands can cause a physiological stress response, and may compromise welfare. The objective of the current study was to investigate relationships that noseband tightness has with oral behavior and with physiological changes that indicate a stress response, such as increases in eye temperature (measured with infrared thermography) and heart rate and decreases in heart rate variability (HRV). Horses (n = 12) wearing a double bridle and crank noseband, as is common in dressage at elite levels, were randomly assigned to four treatments: unfastened noseband (UN), conventional area under noseband (CAUN) with two fingers of space available under the noseband, half conventional area under noseband (HCAUN) with one finger of space under the noseband, and no area under the noseband (NAUN). During the tightest treatment (NAUN), horse heart rate increased (P = 0.003), HRV decreased (P < 0.001), and eye temperature increased (P = 0.011) compared with baseline readings, indicating a physiological stress response. The behavioral results suggest some effects from bits alone but the chief findings are the physiological readings that reflect responses to the nosebands at their tightest. Chewing decreased during the HCAUN (P < 0.001) and NAUN (P < 0.001) treatments. Yawning rates were negligible in all treatments. Similarly, licking was eliminated by the NAUN treatment. Following the removal of the noseband and double bridle during the recovery session, yawning (P = 0.015), swallowing (P = 0.003), and licking (P < 0.001) significantly increased compared with baseline, indicating a post-inhibitory rebound response. This suggests a rise in motivation to perform these behaviors and implies that their inhibition may place horses in a state of deprivation. It is evident that a very tight noseband can cause physiological stress responses and inhibit the expression of oral behaviors.